2023
DOI: 10.1139/cjpp-2022-0341
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Akt/FoxO3 signaling pathway enhances oxidative stress-induced autophagy and alleviates brain damage in a rat model of ischemic stroke

Abstract: Autophagy has been implicated in stroke. Our previous study showed that the FoxO3 transcription factor promotes autophagy after transient cerebral ischemia/reperfusion (I/R). However, whether the Akt/FoxO3 signaling pathway plays a regulatory role in autophagy in cerebral I/R-induced oxidative stress injury is still unclear. The present study aims to investigate the effects of the Akt/FoxO3 signaling pathway on autophagy activation and neuronal injury in vitro and in vivo. By employing LY294002 or insulin to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In their latest study, Deng et al indicated that Akt/FoxO3 signaling pathway activation inhibited oxidative stress-mediated cell death through activation of autophagy. Their study supported a critical role for the Akt/FoxO3 signaling pathway in autophagy activation in stroke (Deng et al, 2023). The remaining 12 genes (RPS2, CKS2, COMMD8, CDK19, KAT6A, CBL, CBX1, COPS2, SNX16, CCNG1, FHL2, and CNIH1) have not been reported to be associated with IS.…”
Section: Discussionmentioning
confidence: 81%
“…In their latest study, Deng et al indicated that Akt/FoxO3 signaling pathway activation inhibited oxidative stress-mediated cell death through activation of autophagy. Their study supported a critical role for the Akt/FoxO3 signaling pathway in autophagy activation in stroke (Deng et al, 2023). The remaining 12 genes (RPS2, CKS2, COMMD8, CDK19, KAT6A, CBL, CBX1, COPS2, SNX16, CCNG1, FHL2, and CNIH1) have not been reported to be associated with IS.…”
Section: Discussionmentioning
confidence: 81%